Temporalities of Modernism - Borbély, Carmen; Mihálycsa, Erika; Petrar, Petronia (Ledizioni, 2022)
Temporalities of Modernism gathers fourteen scholars whose contributions readdress the very tenets of modernism by approaching its multifaceted relationship with time in a series of fresh and original essays. The contemporary energies behind the collection are rooted in the turbulence of the modernist age: relativity, irreversibility, duration, fragmentation, contingency, and the looming threat of the apocalyptic future. The collection includes geographical areas often neglected by the habitual reduction of modernist studies to English-speaking literary high modernism, or to the concentration of famous figures in the traditional capital of modernism-Paris. Thus it offers detailed presentations of Italian pre-WWI modernism, Czech Dadaism, or of Polish, Romanian, and Hungarian writers and artists. The borders also open in terms of genres and mediums, as the contributions are not limited to fiction, but examine the multi-faceted productions of modernist artists: poetry, theatre, painting, music, cinema, photography, etc. In addition, the limits are temporally stretched out as some contributions focus on more recent writers (such as Sylvia Plath) and their reactivation of modernist discoveries.